An Analysis of Apology Strategies Used by Characters in Inside Out Movie - Farhan, Wildan; Pradipta, Bramantya (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Apology is crucial in communication for maintaining social harmony and resolving conflicts. This research examines apology strategies used by characters in the 2016 Oscar-winning animated movie "Inside Out." The objectives are to identify the coding schemes of apology strategies in the characters' utterance and determine the most dominant ones. Using Klimczak and Pawlak's (2014) theory and a qualitative descriptive method, data were collected by analyzing the characters' utterances in the movie. Employing a micro-linguistic pragmatic approach, the study reveals that direct apology strategies are predominantly used, influenced by factors like the severity of the infraction, social status, and cultural background. After analyzing the apology strategies in "Inside Out," researchers found 90 utterances: Illocutionary Force Indicating Device (IFID) with 18 appearances, Explanation or account of the situation (EXPL) with 17 appearances, Internal intensifiers (INT) with 11 appearances, Promise of Forbearance (FORB) with 10 occurrences, Offer of Repair (REPR) with 7 occurrences, Phatic communion (PC) with 5 occurrences, and the most dominant, Acknowledgment of responsibility (RESP), with 22 occurrences. The methodology involved qualitative observation and analysis of the movie, categorizing and coding the apology strategies. The study underscores the importance of direct apologies in animated films and their impact on interpersonal relationships and character development, contributing to the theoretical understanding of apology strategies and offering practical insights for further research in pragmatics and communication studies. Future research could explore more genres and contexts to validate and expand these findings.